Impact of Early Marriage on the Personality Development of Girls: A Review - Khadka, Kalpana (NPRC Journal of Multidisciplinary Research, 2025)
Background: Early marriage, affecting one in five girls globally, is a critical human rights and developmental issue. While its detrimental effects on health and education are well-documented, its impact on adolescent personality development—a period crucial for identity formation, autonomy, and emotional regulation—remains an understudied area. This review addresses this gap by synthesizing evidence on how early marriage influences the psychosocial and personality trajectories of girls.Objectives: This review aims to synthesize recent empirical evidence on the impact of early marriage on girls' personality development, identify the key mechanisms underlying this relationship, highlight critical evidence gaps, and propose directions for future research and policy.Methods: A targeted narrative review was conducted using peer-reviewed literature from 2019 to 2025, sourced from databases including PubMed, BMC journals, The Lancet, and UNICEF evidence reviews. The search focused on studies measuring psychosocial and personality-relevant outcomes such as self-efficacy, autonomy, mental health, and identity. A thematic synthesis was performed, prioritizing longitudinal and mixed-methods studies where available.Findings: The synthesis reveals that early marriage adversely affects personality development through multiple interconnected pathways: (1) Educational interruption, which constrains identity exploration and limits the development of traits like openness and conscientiousness; (2) Reduced autonomy and agency, hindering the formation of an independent self-concept and internal locus of control; (3) Elevated mental health vulnerabilities, including depression and anxiety, which shape emotional stability and neuroticism; and (4) Exposure to intimate partner violence and trauma, which alters interpersonal trust, coping strategies, and stress regulation. While evidence for these indirect pathways is strong, a direct measurement of personality trait change is scarce due to methodological limitations.Conclusion: Early marriage is a significant social determinant that disrupts normative personality development by truncating adolescence and exposing girls to environments that stifle psychosocial growth. The findings underscore that the consequences extend beyond physical health and economics to the core psychological development of individuals.Implication: There is an urgent need for holistic interventions that integrate psychosocial support with existing efforts to delay marriage and keep girls in school. Future research must employ longitudinal designs with culturally adapted personality measures to establish causality and track trait-level changes, informing more effective policies to safeguard girls' developmental potential.